Impurity dynamics in tokamak like magnetic configuration with X-point - Moskvitin, A.O.; Shishkin, A.A. (Вопросы атомной науки и техники, 2008)
Expressions for plasma flow velocities are obtained in invariant form in non ideal MHD approach. Simulation of plasma flow trajectories in tokamak like magnetic configuration with X-point is carried out. The method of plasma flow regulating in the vicinity of separatrix by varying divertor coil current is proposed. To sustain MHD simulation the impurity ion Newton-Lorentz simulations near X-point are carried out.